Optimization strategy of multi-link energy efficient joint transmission of Wi-Fi 7 - Linyan DAI; Xuming FANG; Rong HE (物联网学报)
In the multi-link non-simultaneous transmit and receive mode of next-generation Wi-Fi 7 protocol, the transmission ending time of multi-link device (MLD) needs to be aligned on each link, which may require data padding, resulting in the waste of spectrum resources and transmission energy consumption.A high energy efficient MLD transmission algorithm was proposed to improve the total energy efficiency of MLD station (STA) on the premise of meeting the data transmission delay limit.The proposed algorithm was optimized from the following three aspects: link data distribution ratio, communication resource allocation and STA transmission power.Simulation results show that the proposed algorithm can reduce energy consumption by reducing padding data on the premise of guaranteeing the delay limit of data transmission, and the transmission energy efficiency of the system is increased by about 150% compared with that of the baseline scheme.